Factors influencing menstrual hygiene knowledge, attitudes, and practices among adolescent girls in African rural schools: scoping review - Tshivule, Mosotho Zenia; Rasweswe, Molatelo Melitah; Mothiba, Tebogo Maria; Bopape, Mamare Adelaide (Frontiers in Reproductive Health, 2025)
Menstrual hygiene management (MHM) is a critical component of adolescent health and well-being, particularly in rural African schools where cultural, economic, and infrastructural challenges persist. This scoping review followed the steps proposed by Arksey and O'Malley to explore the factors influencing menstrual hygiene knowledge, attitudes, and practices among adolescent girls in rural African settings. The review systematically analysed literature conducted in diverse African rural public schools. Findings reveal that many adolescent school girls lack comprehensive knowledge about menstruation, due to unreliable or insufficient sources of menstrual hygiene management information and unpreparedness for menarche. Furthermore, their menstrual hygiene practices are shaped by various sociocultural and religious influences. There is also resource limitation, related to availability and cost of menstrual hygiene management supplies, and water, sanitation, and hygiene (WASH) infrastructure in rural schools. These challenges have a significant impact on school attendance, academic performance, and the overall quality of life for adolescent girls. The review practice. It emphasizes the importance of multi-sectoral approaches in supporting adolescent girls in rural African schools and advocates for further research to address persistent knowledge and practice gaps. There is also a need for integrated interventions, including menstrual health education, improved WASH infrastructure, and the provision of affordable menstrual products. Addressing these factors holistically can enhance menstrual hygiene management, reduce stigma, and promote gender equality in education.